2013
DOI: 10.1021/pr400101t
|View full text |Cite
|
Sign up to set email alerts
|

LC–MS/MS Identification of the O-Glycosylation and Hydroxylation of Amino Acid Residues of Collagen α-1 (II) chain from Bovine Cartilage

Abstract: O-Glycosylation of collagen is a unique type of posttranslational modifications (PTMs), involving the attachment of galactose (Gal) or glucose-galactose (Glc-Gal) moieties to hydroxylysine (HyK). Also, hydroxyproline (HyP) result from the posttranslational hydroxylation of some proline residues in collagen. Here, LC-MS/MS was effectively employed to identify 23 O-glycosylation sites and a large number of HyP residues associated with bovine type II collagen α-1 chain (CO2A1). The modifications of the 23 O-glyco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
47
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(51 citation statements)
references
References 60 publications
(121 reference statements)
4
47
0
Order By: Relevance
“…Hyp occurs exclusively at position y (Fietzek and Rauterberg 1975), recent studies showed that Hyp also occurs at position x in fibrillar collagens (Song and Mechref 2013;Weis et al 2010).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Hyp occurs exclusively at position y (Fietzek and Rauterberg 1975), recent studies showed that Hyp also occurs at position x in fibrillar collagens (Song and Mechref 2013;Weis et al 2010).…”
Section: Discussionmentioning
confidence: 98%
“…The presence of Hyp at both positions x and y by contrast, further stabilized the triple helical conformation of the peptides (Berisio et al 2004). The detection of several Hyp residues at position x on various types of collagen makes it difficult to predict the positional impact of Hyp on the thermal stability of more complex polypeptides (Bann and Bachinger 2000;Buechter et al 2003;Song and Mechref 2013). Although early work demonstrated that…”
Section: Discussionmentioning
confidence: 99%
“…38 A total of five MS/MS data sets were collected, containing 12 908 CID, 13 986 HCD, and 1 937 ETD MS/MS spectra. 7 …”
Section: Mass Spectrometry Experimentsmentioning
confidence: 99%
“…Following the preprocessing steps in Ref. 7, noise peaks were removed using a signal-to-noise ratio 1.5, and MS/MS spectra without peaks were removed.…”
Section: Glycopeptide Identificationmentioning
confidence: 99%
See 1 more Smart Citation